“What’s COVID-19 Vaccine Like?” – From A Cognitive Frame to A Similative Proposition - Nino Guliashvili (European Scientific Journal, ESJ, 2023)
Frames and propositions are believed to be cognitive acts that play an important role in the perception of reality and the enactment of discursive practices. The linguistic scrutiny of the Covid-19 pandemic discourse could shed light on how the figurative language, similes in particular, are conceptualized by the cognitive structures and represented discursively as surface-level manifestations of the pandemic reality. This paper argues that similes as opposed to metaphors explicitly expound propositions and communicative frames in the discourse to avoid incipient cognitive ambiguity of the comparison. As it appears, similes may come forward as more tangible cognitive-discursive structures that assist the human mind to cope with the novel cognitive comparisons.